Hyper-conventional, unconventional, or “just right”? The interplay of normalisation and cross-linguistic influence in the use of modal particles in translated Chinese children’s literature - Zhang, Xiaomin; Kotze, Haidee; Fang, Jing (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2022)
The interplay between normalisation and cross-linguistic influence (CLI) has not been widely investigated in the specialised text type of children’s literature. Yet it may be proposed that normalisation would be particularly salient in translated children’s books as a consequence of the importance assigned to the needs of the target audience. This study embarks on an investigation of normalisation in Chinese children’s literature translated from English using modal particles as operationalisation. We first propose that a conceptual and empirical distinction needs to be drawn between normalisation and over-normalisation (or hyperconventionality), and that these are in tension with CLI. By combining quantitative and qualitative analysis, we then aim to shed light on whether translators tend to (over-)normalise children’s books to the norms of the genre in the recipient culture, or whether there is evidence of CLI effects that make the target texts more unconventional in this respect. Overall, the study finds evidence for normalisation, but not over-normalisation, with translated Chinese children’s books and non-translated Chinese children’s books largely similar in this respect. However, a small-scale qualitative analysis of two modal particles suggests that CLI and translators’ style play a role in some observable differences between translated and non-translated Chinese children’s books.